1983
DOI: 10.3181/00379727-173-41651
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Virus-Induced Diabetes Mellitus by Interferon is Influenced by the Host Strain

Abstract: The diabetogenic variant of encephalomyocarditis virus (EMC-D) induces a diabeteslike syndrome in certain strains of mice. A study was done to determine if virus-induced diabetes could be prevented by interferon (IFN). It was found that the production of diabetes by EMC-D was blocked by either IF", or a variety of IFN-inducers in SWR/J, but not ICR Swiss mice. The replication of EMC-D in cell culture was inhibited by IFN,. It is concluded that the response of pancreatic beta cells to the protective effect of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Mice were infected by intraperitoneal (i.p.) injection with 800 plaque‐forming units of EMCV‐D 44 . Glucose tolerance tests (GTT) were performed by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were infected by intraperitoneal (i.p.) injection with 800 plaque‐forming units of EMCV‐D 44 . Glucose tolerance tests (GTT) were performed by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…CD1d1 molecules and NKT cells have been shown to be important in other virus infections as well, particularly with regard to virus-mediated pathology. For example, an encephalomyocarditis virus (EMCV) infection of normal mice results in diabetes and CNS effects in a subset of those mice infected (57)(58)(59)(60)(61). When CD1KO mice are infected with EMCV, a substantially greater percentage of mice develop both diabetes and paralysis (62).…”
Section: Figurementioning
confidence: 99%
“…Furthermore, the D variant was in a linear phase of attachment over the range of MOI tested, whereas that of EMC-B virus was nearly saturated at a low MOI. this hypothesis (6). 3).…”
Section: Attachment Of Encephalomyocarditis (Emc)-d and Emc-b Virusmentioning
confidence: 84%
“…Be-cause it has been shown that EMC-B virus is a good inducer of interferon (IFN), whereas EMC-D virus induces little or no IFN (1), it has been suggested that IFN produced during the early stages of EMC-B virus infection plays a role in protecting the p-cells from viral destruction. Indeed, we have evidence and have reported that exogenously administered IFN-a and -3 or poly I:C protects SWR/J but not ICR Swiss mice against the diabetogenic effects of EMC-D virus (6). For example, Gadzik et al (4) reported that a single injection of the IFN-inducer polyinosinic-polycytidylic acid (poly I:C) protects SWR/J mice against the diabetogenic effects of EMC-M virus, an EMC virus from which both the D and B variants were isolated (1).…”
mentioning
confidence: 86%